Large-scale integration of single-cell transcriptomic data captures transitional progenitor states in mouse skeletal muscle regeneration - David W. McKellar (Nature Portfolio, 2021)
David McKellar et al. integrate single-cell and -nuclear transcriptomic analyses of mouse skeletal muscle in homeostatic conditions or following injury. The resulting transcriptomic model of myogenesis identified rare, transitional states and cell subtypes that are poorly represented in individual datasets, providing a valuable resource for the field.